Diversity Matters : The Economic Geography of Industry Location in India - Lall, Somik V.; Koo, Jun; Chakravorty, Sanjoy (World Bank, Washington, DC, 2014)
How does economic geography influence industrial production and thereby affect industrial location decisions and the spatial distribution of development? For manufacturing industry, what are the externalities that matter, and to what extent? Are these externalities spatially localized? The authors answer these questions by analyzing the influence of economic geography on the cost structure of manufacturing firms by firm size for eight industry sectors in India. The economic geography factors include market access and local and urban externalities-which are concentrations of own-industry firms, concentrations of buyer-supplier links, and industrial diversity at the district (local) level. The authors find that industrial diversity is the only economic geography variable that has a significant, consistent, and substantial cost-reducing effect for firms, particularly small firms. This finding calls into question the fundamental assumptions regarding localization economies and raises further concerns on the industrial development prospects of lagging regions in developing countries.